2014
DOI: 10.1007/s11684-014-0324-4
|View full text |Cite
|
Sign up to set email alerts
|

Generation and repair of AID-initiated DNA lesions in B lymphocytes

Abstract: Activation-induced deaminase (AID) initiates the secondary antibody diversification process in B lymphocytes. In mammalian B cells, this process includes somatic hypermutation (SHM) and class switch recombination (CSR), both of which require AID. AID induces U:G mismatch lesions in DNA that are subsequently converted into point mutations or DNA double stranded breaks during SHM/CSR. In a physiological context, AID targets immunoglobulin (Ig) loci to mediate SHM/CSR. However, recent studies reveal genome-wide a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 184 publications
(321 reference statements)
0
30
0
Order By: Relevance
“…SHM and CSR each require activation induced deaminase (AID). AID deaminates cytosine (C) in single-stranded (ss) DNA and converts it into uracil (U), resulting in U:G mismatch lesions (3, 6). However, it remains unclear how AID-initiated lesions are preferentially converted into point mutations during SHM versus DSBs during CSR.…”
Section: Introductionmentioning
confidence: 99%
“…SHM and CSR each require activation induced deaminase (AID). AID deaminates cytosine (C) in single-stranded (ss) DNA and converts it into uracil (U), resulting in U:G mismatch lesions (3, 6). However, it remains unclear how AID-initiated lesions are preferentially converted into point mutations during SHM versus DSBs during CSR.…”
Section: Introductionmentioning
confidence: 99%
“…Cγ, Cε, and Cα), respectively (1). The essential molecular components of CSR include: (1) active germline transcription of C H genes that renders a given C region accessible for recombination (1, 3, 4); (2) switch (S) regions that are highly repetitive and specific DNA sequences, located 5’ of each set of C H exons except Cδ (5); (3) activation induced deaminase (AID) that deaminates cytosine (C) and converts it into uracil (U), thereby resulting in U:G mismatch; (4) subsequent recognition and processing of the AID-initiated U:G mismatch by mismatch repair (MMR) and base excision repair (BER) pathways that generate DNA double strand breaks (DSBs) in the upstream donor Sμ and a downstream acceptor S region (6, 7); (5) repair of the AID-initiated DSBs via non-homologous end-joining (NHEJ) that eventually completes CSR via re-joining the two broken S regions (8, 9). Both classical and alternative NHEJ contribute to the repair of S region DSBs (8, 9).…”
Section: Introductionmentioning
confidence: 99%
“…In the previous model, we found that the inserted Sγ1 region mutated at a 10 fold higher frequency than the intronic sequence of Bcl6 (39). While S region sequences are indeed optimal targets of AID in the context of the Igh locus (18, 30), we propose that the capacity of such sequences to increase the frequency of mutations or DSBs at a given locus is dependent on the “genomic context” of the particular locus. However, genomic context represents a broad concept; to define its specific influence on AID-mediated mutagenesis, we propose that locus-specific cis regulatory elements probably account for the disparity between c-myc and Bcl6 loci in terms of AID targeting.…”
Section: Discussionmentioning
confidence: 91%